2021
DOI: 10.3390/cancers13153710
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Hepatocellular Carcinoma Incidence and Risk Factors among a Low Socioeconomic Population

Abstract: The purpose of this study was to examine differences in risk factors associated with hepatocellular carcinoma (HCC) among White and African Americans from low socioeconomic backgrounds in the Southern Community Cohort Study (SCCS). The SCCS is a prospective cohort study with participants from the southeastern US. HCC incidence rates were calculated. Multivariable Cox regression was used to calculate HCC-adjusted hazard ratios (aHR) associated with known baseline HCC risk factors for White and African Americans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…At-risk populations, including racial/ethnic minorities, have increased rates of HCC and poorer outcomes due to individual and area-level disparities in risk factors, screening, and treatment ( 13 , 19 23 ). Multilevel interventions are likely needed to address the racial and economic disparities that contribute to liver cancer incidence and survival, such as differences in access to general healthcare that may impact screening and treatment for upstream risk factors such as alcohol use, obesity, and injection drug use.…”
Section: Discussionmentioning
confidence: 99%
“…At-risk populations, including racial/ethnic minorities, have increased rates of HCC and poorer outcomes due to individual and area-level disparities in risk factors, screening, and treatment ( 13 , 19 23 ). Multilevel interventions are likely needed to address the racial and economic disparities that contribute to liver cancer incidence and survival, such as differences in access to general healthcare that may impact screening and treatment for upstream risk factors such as alcohol use, obesity, and injection drug use.…”
Section: Discussionmentioning
confidence: 99%
“…Mahimpundu et al 71 reported a higher incidence of HCC among African Americans (10.2 per 100 000), compared to Caucasian Americans (6.3 per 100 000) 143 . The etiological factors of HCC were also found to be disproportionate, as the causative factors for HCC in African Americans were tobacco and alcohol use, compared to HCV infection and diabetes for Caucasian Americans 26 . Individuals of Hispanic ethnicity in the United States had the highest prevalence of NAFLD, with a high risk of progression to NASH 152 .…”
Section: Geographical and Ethnic Disparity In Hccmentioning
confidence: 99%
“… 143 The etiological factors of HCC were also found to be disproportionate, as the causative factors for HCC in African Americans were tobacco and alcohol use, compared to HCV infection and diabetes for Caucasian Americans. 26 Individuals of Hispanic ethnicity in the United States had the highest prevalence of NAFLD, with a high risk of progression to NASH. 152 Immigration has been postulated to play a major role in the higher rates of HCC within ethnic minorities in the United States, Western Europe, Australia, and Canada.…”
Section: Geographical and Ethnic Disparity In Hccmentioning
confidence: 99%
See 2 more Smart Citations